The role of the PTPRC (CD45) mutation in the development of multiple sclerosis in the North West region of the United Kingdom. - Nicholas,RS; Partridge,J; Donn,RP; Hawkins,C; Boggild,MD (J Neurol Neurosurg Psychiatry, 2003)
BACKGROUND: A point mutation in protein tyrosine phosphatase receptor, type c polypeptide (PTPRC) has been associated with familial multiple sclerosis. This CG mutation at position 77 of exon 4 results in altered expression of CD45 isoforms on immune cells. OBJECTIVE: To study the incidence of PTPRC mutations in subjects with multiple sclerosis in the North West region of the United Kingdom. METHODS: Affected and unaffected subjects from five pedigrees with familial multiple sclerosis, 330 non-familial cases of multiple sclerosis, and 197 controls were studied. Genomic DNA was amplified using CD45IE34 and CD45IE44 primers, digested with Mspl, and run on an agarose gel. Polymerase chain reaction products were sequenced to exclude any other mutations. RESULTS: No PTPRC exon 4 genomic mutations were seen in any of the five families. In the non-familial cases the incidence of mutation was 4.1% in 197 controls and 5.1% in 330 multiple sclerosis patients. No significant association was found in this study with this mutation and disease susceptibility, sex, or an extended disability scale score of < 5.5. CONCLUSIONS: This candidate does not appear to influence the development of familial multiple sclerosis in this population. The negative result could arise from a type II error owing to the number of families and non-familial cases screened. Alternatively it might suggest that the contribution of the PTPRC mutation depends upon the genetic background.